The Effect of Chicory on Bilirubin Level in Newborns Suffering From Jaundice: A Systematic Review - Moloud Fakhri; Amirsaeed Hosseini; Roya Farhadi; Mahmood Moosazadeh; Mohammad Azadbakht; Vahidreza Berneti (Mazandaran University of Medical Sciences, 2023)
Background: Jaundice is the most prevalent reason for infants' hospitalization during their first month of birth, and herbal medicine has long been used alongside phototherapy to treat this problem.  Objectives: The present systematic review investigates chicory's influence on bilirubin levels in infants with jaundice.  Methods: In this systematic review study, Iranian databases, including Barekat Gostar, Scientific Information Database (SID), Irandoc, and Magiran, along with international databases, including Cochrane Library, Web of Science, Scopus, PubMed, and Google Scholar search engines were explored with relevant keywords to retrieve pertinent studies.  Results: Among the 7 selected articles with a sample size of 408 (204 people in the intervention group and 204 in the control group) from 2006 to 2020, 4 studies were in vitro and 3 were randomized clinical trials. Among these studies, mothers' pregnancy duration ranged between 30.9 and 38.8 weeks, infants' age ranged between 3 and 7 days, and their weight ranged between 1544 and 3316 g. Although chicory administration varied across the studies, 4 studies reported its effectiveness in reducing infants' bilirubin, whereas the other 3 articles reported no effect of chicory on bilirubin levels in infants.  Conclusions: Iran was the only country that evaluated the effect of chicory on neonatal jaundice in the form of several research studies. However, due to the limited number of studies and the different dosages of chicory, the way of consuming chicory, the type of studies, and the age and weight of babies, we could not reach a general conclusion on the efficacy of chicory.